Useing of balanced scorecard measures to enhance the competitive advantage in economic units by applying to the "Rikan" factory for the production of concrete blocks - Ghazi Othman Mahmmod; Hazim Hashim Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The research aims to study the use of balanced scorecard measures to enhance the competitive advantage and the research relied on the practical method to test the research hypotheses and achieve its objectives through the application of measures (financial and non-financial) of the method of balanced scorecard on the actual data "Rikan" factory for the production of concrete blocks Balanced performance has been reached several results, the most important of which are: the traditional financial measures have become inappropriate and do not comply with the requirements of the modern manufacturing environment because they focus primarily on financial results only without attention to the causes of performance, in addition to its Static internal, and modern manufacturing environment is a highly mobile environment is not enough only financial measures, but need other non-financial measures commensurate with the modern environmental variables and current competition conditions. Based on the results of the research, the researchers made several recommendations, the most important of which are: Awareness and consolidation of serious conviction among the management of economic units and workers at all administrative and technical levels of the importance of applying the balanced scorecard method in the economic unit, including the laboratory sample research.